A study of hydrogen embrittlement (HE) on tempered carbon steel - 430260 Astuty Amrin; Yusri Abu Bakar @ Yusof; Ali Ourdjini; Scientific Conference [of] Electron Microscopy Society Malaysia (5th : 1995 : Selangor)
51